ChemInform Abstract: An Easy Access to Fused Chromanones via Rhodium Catalyzed Oxidative Coupling of Salicylaldehydes with Heterobicyclic Olefins. Issue 43 (7th October 2016) - Vijayan, Ajesh; Baiju, T. V.; Jijy, E.; Prakash, Praveen; Shimi, M.; Joseph, Nayana; Pihko, Petri M.; Varughese, Sunil; Radhakrishnan, K. V.
Abstract: Diazabicyclic and urea‐derived bicyclic olefins react with salicylaldehydes to produce various types of fused chromanone systems of biological interest in a single step (mechanism).